2002
DOI: 10.1093/humrep/17.6.1554
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cigarette smoking on human semen parameters and hormones

Abstract: Smoking does not affect conventional semen parameters, but significantly increases round cells and leukocytes. Only a few idiopathic infertile smokers were able to quit smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
124
4
14

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(160 citation statements)
references
References 24 publications
18
124
4
14
Order By: Relevance
“…In literature, there are several cross-sectional studies about the effects of active or passive smoking on semen quality or testicular hormone levels, but most of which have included adolescent or adult patients or have been done in rats. 12,14,17,18 Some studies have shown a negative effect of smoking on semen quality in terms of the conventional semen characteristics whereas others could not demonstrate such an effect. 12,17 Furthermore, it has not been clarified whether smoking has an impact on levels of male reproductive hormones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In literature, there are several cross-sectional studies about the effects of active or passive smoking on semen quality or testicular hormone levels, but most of which have included adolescent or adult patients or have been done in rats. 12,14,17,18 Some studies have shown a negative effect of smoking on semen quality in terms of the conventional semen characteristics whereas others could not demonstrate such an effect. 12,17 Furthermore, it has not been clarified whether smoking has an impact on levels of male reproductive hormones.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,17,18 Some studies have shown a negative effect of smoking on semen quality in terms of the conventional semen characteristics whereas others could not demonstrate such an effect. 12,17 Furthermore, it has not been clarified whether smoking has an impact on levels of male reproductive hormones. Significantly increased, 12 decreased and unchanged levels of total testosterone in male smokers have been reported in various studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A receptor for androgens has been reported to occur in NSCLCs (Beattie et al, 1985;Kaiser et al, 1996) and there may be cooperative interaction between the hormones and active mutations of EGFR during the development of lung cancer. Previous reports have suggested that smoking increases the levels of androgens in men and women (Law et al, 1997;Trummer et al, 2002) and carcinogens from cigarette smoke may disrupt androgen function by reducing androgen receptor (AR) levels in androgenresponsive organs (Lin et al, 2004).…”
mentioning
confidence: 99%